In Vitro Activity of LY127935 - Fass, Robert J. (1979)
LY127935 is a unique new β-lactam antibiotic. Its activity against 536 clinical isolates was studied by using microdilution methods of susceptibility testing and compared with the activities of cefamandole, cefoxitin, and cephalothin. The lowest concentrations required to inhibit at least 90% of strains tested (MIC(90)s) of LY127935 for Staphylococcus aureus, Streptococcus pyogenes, Streptococcus agalactiae, and Streptococcus pneumoniae ranged from 2 to 8 μg/ml. The MIC(90)s for other staphylococci and streptococci were higher. The MIC(90)s for Enterobacteriaceae and Pseudomonas species ranged from 0.12 to 8 μg/ml and 8 to >32 μg/ml, respectively. The MIC(90)s for anaerobes ranged from 2 to >32 μg/ml. As determined by MIC(90)s, LY127935 was consistently the least active antibiotic against facultatively anaerobic gram-positive cocci and the most active against aerobic and facultatively anaerobic gram-negative bacilli. Its position with respect to activity against anaerobes varied from being the most active against Bacteroides fragilis and Clostridium perfringens to the least active against anaerobic cocci. In a population of multidrug-resistant isolates, concentrations of 8 μg or less of LY127935 per ml inhibited 82% of Enterobacteriaceae; concentrations of 32 μg or less per ml inhibited 100% of Enterobacteriaceae and 40% of P. aeruginosa. Increasing the inoculum size by 100-fold did not increase the minimal inhibitory concentrations of LY127935 or cefoxitin but did increase minimal inhibitory concentrations of cefamandole and cephalothin for some Enterobacteriaceae. All four drugs were bactericidal; minimal bactericidal concentrations were the same or one concentration higher than minimal inhibitory concentrations for 91 to 96% of strains tested. The broad spectrum and marked in vitro activity of LY127935 make it a promising new antibiotic.